Sin2x Cos2x
1. sin2x = 2.sinx.cosx Eşitliğinin İspatı 2. cos2x = 2.(cosx)² - 1, cos2x = 1 - 2.(sinx)² ve cos2x = (cosx)² - (sinx)² Eşitliğinin İspatı a. cos2
![Picture of the Pow](/_next/image?url=https%3A%2F%2Fbylge-images.s3.amazonaws.com%2Fbanff-4331689_1920.jpg&w=3840&q=75)
Pow
@pow1. sin2x = 2.sinx.cosx Eşitliğinin İspatı
2. cos2x = 2.(cosx)² - 1, cos2x = 1 - 2.(sinx)² ve cos2x = (cosx)² - (sinx)² Eşitliğinin İspatı
a. cos2x = 2.(cosx)² - 1 Eşitliğinin İspatı
b. cos2x = 1 - 2.(sinx)² Eşitliğinin İspatı
c. cos2x = (cosx)² - (sinx)² Eşitliğinin İspatı
Published Date:
May 01, 2020
Updated Date:
December 12, 2023